Antibacterial activity evaluation and mode of action study of novel thiazole-quinolinium derivatives. Issue 25 (16th April 2020) - Li, Ying; Sun, Ning; Ser, Hooi-Leng; Long, Wei; Li, Yanan; Chen, Cuicui; Zheng, Boxin; Huang, Xuanhe; Liu, Zhihua; Lu, Yu-Jing
Abstract : A new series of thiazole-quinolinium derivatives perturb the polymerization of FtsZ with strong antibacterial activities. Abstract : New antimicrobial agents are urgently needed to address the emergence of multi-drug resistant organisms, especially those active compounds with new mechanisms of action. Based on the molecular structures of the FtsZ inhibitors reported, a variety of thiazole-quinolinium derivatives with aliphatic amino and/or styrene substituents were synthesized from benzothiazolidine derivatives. In the present study, to further explore the antibacterial potential of thiazole-quinolinium derivatives, several Gram-positive and Gram-negative bacteria were treated with the newly modified compounds and the biological effects were studied in detail in order to understand the bactericidal action of the compounds. Our findings reveal that some of these derivatives possess good potent bactericidal activity as they can inhibit Gram-positive methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus and also some Gram-negative organisms and NDM-1 Escherichia coli . Furthermore, compounds 4a1–4a4 and 4b1–4b4 altered the morphology of bacterial cells and the cells displayed a more-elongated shape compared to the untreated cells. Biochemical assays showed that 4a4 and 4b4 stimulate FtsZ polymerization in bacterial cells, which eventually disrupts its dynamic assembly and Z-ring formation. The inhibition of this crucial step in bacterial cell division could potentially represent their main mechanism of antibacterial activity. Cytotoxicity assay and hemolysis assay suggested that 4a4 and 4b4 possess low cytotoxicity. In summary, these results further highlight the importance of 4a4 and 4b4 that could be developed as potent and effective bacteriostatic agents against multi-drug resistant bacteria.